Determination of value price or computer application using function point analysis method - Didik Suwito Pribadi (Sekolah Tinggi Ilmu Komputer Binaniaga, 2019)
Some developer very capable of developing good quality working applications, but they donâ€™t have the right value and price for their products, and it is because they did not use the right method to calculate the size of the product and valuate them correctly, most of them use analogy and expert judgment to perform their product sizing and valuation. This situation will create inconsistency in doing the pricing and it will create disadvantagesÂ for both developers and users. Function point analysis provides a methodology to perform software size calculation using algorithmic approaches that givesÂ comprehensive and consistent results. In this document, I will explain step by step theÂ processes of calculating the Function point using FPA procedures by implementing calculationÂ formula of EI, EO, EQ, ILF, EIF, and VAP. I also will implement them to calculateÂ the size of the â€œXIbarâ€ application system, especially module customer care and customerÂ info. By doing all these activities I hope will provide simple templates and proceduresÂ for calculating the size of application software that can be used easily by developers, students, and others who need it.